English Guiding Video for “Visa on Arrival Extension in One Day Service “at Cilacap Class I Immigration Office - Rafif Dzaky Alauddin Cahya (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2023)
The job training, at Cilacap Class I Immigration Office, Central Java, wascarried out from April 3rd, 2023 to May 3rd, 2023. The main task was producinga guiding video of